1994
DOI: 10.1111/j.1540-8159.1994.tb03792.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐Years Experience with Intravascular Lead Extraction

Abstract: From December 1988 to April 1994, the extraction of 2,195 intravascular pacing leads from 1,299 patients was attempted at 193 centers. Indications were: infection (54%, including 10% septicemia), pacemaker reoperation with removal of nonfunctional or incompatible leads (40%), and other causes (6%). Extraction was attempted via the implant vein using locking stylets and dilator sheaths, via the femoral vein using snares, retrieval baskets, and sheaths, or via both approaches. Leads had been implanted for 0.2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
188
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(197 citation statements)
references
References 6 publications
6
188
0
3
Order By: Relevance
“…Three polyesterurethane constructs of different porosity were examined; a nonporous solvent cast film, a porous electrospun mesh and a porous phase inversion blockage of ocular drainage devices for glaucoma 25 , malfunctioning of biosensors 26 , excessive shrinkage of surgical meshes for hernia repair 27 and post-operative difficulty in removing intravascular pacing leads 28 . In this study, the tissue-implant interface thickness was significantly maximal for the bovine pericardium and minimal for the mesh at both time points.…”
Section: Discussionmentioning
confidence: 99%
“…Three polyesterurethane constructs of different porosity were examined; a nonporous solvent cast film, a porous electrospun mesh and a porous phase inversion blockage of ocular drainage devices for glaucoma 25 , malfunctioning of biosensors 26 , excessive shrinkage of surgical meshes for hernia repair 27 and post-operative difficulty in removing intravascular pacing leads 28 . In this study, the tissue-implant interface thickness was significantly maximal for the bovine pericardium and minimal for the mesh at both time points.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al 3 have reported the following results obtained from 1988 to 1994 in the U.S. Lead Extraction Database: 86.8% of complete extraction; 7.5% of incomplete extraction; 5.7% of failure; 2.5% of severe complications; and 0.6% of mortality. Byrd et al 4 , analyzing data collected from January 1994 to April 1996 in the same database in a period when these techniques were considered reasonably stabilized, reported the results of extraction of 3,540 leads from 2,338 patients: 93% of complete extraction; 5% of partial extraction; 2% of failure in the procedure, and 1.4% of severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…Non-infectious indications include malfunctioning leads or leads which through their presence can cause harm to the patient (for example thrombosis of the superior vena), as well as leads that have to be removed in order to upgrade a device. In all published reports, infection seems to be the most common indication for lead extraction (54-60% of all extraction procedures) [16,17].…”
Section: Indications For Lead Extractionmentioning
confidence: 99%
“…Calcification of the fibrous tissue may even occur over time especially in young patients [12]. The most common adhesion sites include the venous entry site, the superior vena cava and the electrode-endocardial interface [13]. (Figure 1).…”
Section: Introductionmentioning
confidence: 99%